(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The pathological state of rabbit teeth is very common in clinical practice and can cause complications that can lead to death. Therefore, special attention should be paid to early diagnosis in order to find out in time. X-ray diagnosis is reflected in X-ray examination to evaluate the condition. A method of interpreting X-ray images, comparing the characteristics of other animal species.